Diverse enteric bacterial, viral, and parasitic pathogen genes are shed in animal feces in Indiana - Anna A. Heintzman; Ishi Keenum; Drew Capone (PLoS ONE, 2026)
Southern Indiana has intensive livestock production, yet species-resolved fecal pathogen and pathogen associated gene profiles are limited. At 10 sites in southern Indiana (April–June 2024), we collected 128 fecal specimens from 10 hosts: pigs (n = 12), horses (12), cats (12), chickens (12), dogs (22), white-tailed deer (12), sheep (12), goats (12), cows (12), and humans (10). We extracted and assayed total nucleic acids using a custom 43-target TaqMan Array Card (RT-qPCR). Flotation microscopy was performed on pig and dog stools for helminth ova. In-silico specificity checks were conducted for selected targets due to potential for cross reactivity between pathogen species. Most samples (60%, 75/126) were positive for ≥1 target, including enteropathogenic Escherichia coli ( eae ) 16% and shiga toxin genes ( stx1 10%, stx2 6.3%). Higher prevalence of genes associated with specific pathogens and gut microbes in specific animals was common, including E. coli O157:H7 in pigs (42%) and sheep (8.3%); Campylobacter coli in chickens (36%) and Klebsiella pneumoniae in humans (60%) and dogs (9.1%). We found the protozoa Giardia in 15% of samples (notably dogs 32%, cows 33%) and Cryptosporidium in 14% (cats 55%, cows 25%, chickens 27%). Most (55%) chicken samples were positive for Plasmodium , which aligned with evidence of locally circulating avian haemosporidians. The Ascaris lumbricoides assay was positive only in pigs (17%), and we identified Ascaris type eggs in 92% of pig samples via microscopy, suggesting our Ascaris lumbricoides assay cross reacted with Ascaris suum supporting detection of the swine lineage ( A. suum ). We detected the class 1 integron-integrase gene ( intI1 ) in 43% of stools, concentrated in chickens, pigs, and horses. These findings suggest animal feces poses a public health hazard in Southern Indiana and indicate the need for targeted One Health studies to better understand the public health risks of specific exposures and animal feces management practices (e.g., farm storage capacity, land application timing, soil incorporation/injection, tile-drain proximity).